The use of individual tracking programs in public health: a bioethics dilemma - Ricardo Jardim Neiva; João Felício Rodrigues Neto; Ana Paula Oliveira Nascimento Alves; Patrícia de Sousa Fernandes Queiroz; Leila das Graças Siqueira; Clara Cynthia Melo e Lima; Francisca Souza Santos Dias; Renê Ferreira da Silva-Júnior (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to understand the bioethical perspectives on mobile tracking device use. Methods: theoretical study based on action research, carried out with eight graduate students from a public university. A focus group was used, with a thematic content analysis methodology with a codebook structure, approved by the Research Ethics Committee. Results: from the analysis, there was a concern about using devices after the pandemic ended. Using or not the device, rights inherent to humans, legislation and effectiveness of methods deepen interpretations, moving participants from a personalistic conception of the topic to a vision focused on professional implications about the methods. Final considerations: the debate on the impact of using technological devices on health, especially those that imply restriction of rights that refer to individuals' private life, involves a discussion of a professional nature, in addition to requirement for clear rules on the topic.